Respiratory Bacteria Stabilize and Promote Airborne Transmission of Influenza A Virus - Hannah M. Rowe (American Society for Microbiology, 2020)
ABSTRACT Influenza A virus (IAV) is a major pathogen of the human respiratory tract, where the virus coexists and interacts with bacterial populations comprising the respiratory tract microbiome. Synergies between IAV and respiratory bacterial pathogens promote enhanced inflammation and disease burden that exacerbate morbidity and mortality. We demonstrate that direct interactions between IAV and encapsulated bacteria commonly found in the respiratory tract promote environmental stability and infectivity of IAV. Antibiotic-mediated depletion of the respiratory bacterial flora abrogated IAV transmission in ferret models, indicating that these virus-bacterium interactions are operative for airborne transmission of IAV. Restoring IAV airborne transmission in antibiotic-treated ferrets by coinfection with Streptococcus pneumoniae confirmed a role for specific members of the bacterial respiratory community in promoting IAV transmission. These results implicate a role for the bacterial respiratory flora in promoting airborne transmission of IAV. IMPORTANCE Infection with influenza A virus (IAV), especially when complicated with a secondary bacterial infection, is a leading cause of global mortality and morbidity. Gaining a greater understanding of the transmission dynamics of IAV is important during seasonal IAV epidemics and in the event of a pandemic. Direct bacterium-virus interactions are a recently appreciated aspect of infectious disease biology. Direct interactions between IAV and specific bacterial species of the human upper respiratory tract were found to promote the stability and infectivity of IAV during desiccation stress. Viral environmental stability is an important aspect during transmission, suggesting a potential role for bacterial respiratory communities in IAV transmission. Airborne transmission of IAV was abrogated upon depletion of nasal bacterial flora with topical antibiotics. This defect could be functionally complemented by S. pneumoniae coinfection. These data suggest that bacterial coinfection may be an underappreciated aspect of IAV transmission dynamics.